2012
DOI: 10.1093/nar/gks1278
|View full text |Cite
|
Sign up to set email alerts
|

CHFR is important for the first wave of ubiquitination at DNA damage sites

Abstract: Protein ubiquitination plays an important role in activating the DNA damage response and maintaining genomic stability. In response to DNA double-strand breaks (DSBs), a ubiquitination cascade occurs at DNA lesions. Here, we show that checkpoint with Forkhead-associated (FHA) and RING finger domain protein (CHFR), an E3 ubiquitin ligase, is recruited to DSBs by poly(ADP-ribose) (PAR). At DSBs, CHFR regulates the first wave of protein ubiquitination. Moreover, CHFR ubiquitinates PAR polymerase 1 (PARP1) and reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
79
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(82 citation statements)
references
References 78 publications
3
79
0
Order By: Relevance
“…In a similar study, CHFR overexpressed in cells was demonstrated to be recruited to sites of laser microirradiationinduced DNA damage in a poly(ADP-ribosyl)ation-dependent manner. Poly(ADP-ribosyl)ated PARP-1 was also shown to be a target for CHFR-mediated polyubiquitylation (57). As with RNF4-mediated polyubiquitylation of SUMOylated PARP-1, this suggests a possible mechanism for displacing activated PARP-1 from DNA damage sites, therefore promoting DNA repair.…”
Section: Parp-1mentioning
confidence: 91%
“…In a similar study, CHFR overexpressed in cells was demonstrated to be recruited to sites of laser microirradiationinduced DNA damage in a poly(ADP-ribosyl)ation-dependent manner. Poly(ADP-ribosyl)ated PARP-1 was also shown to be a target for CHFR-mediated polyubiquitylation (57). As with RNF4-mediated polyubiquitylation of SUMOylated PARP-1, this suggests a possible mechanism for displacing activated PARP-1 from DNA damage sites, therefore promoting DNA repair.…”
Section: Parp-1mentioning
confidence: 91%
“…Auto-modified PARP1 recruits a DNA repair scaffold XRCC1 to sites of DNA damage in a PAR-dependent manner (7). The PARP1-XRCC1 complex is subsequently disassembled to marshal the DNA repair activities associated with XRCC1, whereas PARP1 is polyubiquitinylated and degraded (8,9). PARylated PARP1 binds to a conserved PAR-binding motif (PBM) located in one of two BRCA1 C terminus (BRCT) domains of XRCC1 (see Fig.…”
mentioning
confidence: 99%
“…It has been shown that CHFR is important for the first wave of protein ubiquitination at DNA damage sites. 18,19 Similar mechanisms could exist in testes as well. Interestingly, the maintenance of spermatogonial stem cells in adults is defective in both Chfr and Atm knockout male mice.…”
Section: Discussionmentioning
confidence: 88%
“…[14][15][16][17] CHFR is an E3 ubiquitin ligase and participates in DNA damage response. 18,19 It is recruited to DNA damage sites by poly(ADP-ribose) and is important for the first wave of protein ubiquitination there. 19 It functions synergistically with RNF8 to activate ATM in response to DNA damage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation